The importance of sustainable emotions in diversity & inclusion processes - Bruno, Mariella; Summa, Ilaria (Community Notebook. People, Education and Welfare in the Society 5.0, 2022)
The period of pandemic crisis experienced over the last twelve months has highlighted how the theme of emotions and sustainability, understood as environmental, social and economic progress and well-being, has become preponderant over development and diversity & inclusion processes. Speaking in this context of emotional sustainability means referring to the ability to become aware of and better understand our emotions, consciously recognising how they influence our feelings and, in turn, help form the values, beliefs and motivations that give us strength and security.